The Buchenwald child : truth, fiction, and propaganda - Niven, William John 1956- (Studies in German literature, linguistics, and culture, 2007)
Introduction -- The protection of Stefan Jerzy Zweig -- Building the Buchenwald myth -- The genesis and impact of Naked among wolves -- The cinema film of Naked among wolves -- Stefan Jerzy Zweig and the GDR -- The deconstruction of the Buchenwald child myth -- Epilogue